Increased Soluble CD155 in the Serum of Cancer Patients - Iguchi-Manaka, Akiko (PLoS One, 2016)
Emerging evidence suggests that DNAM-1 (CD226) play an important role in the recognition of tumor cells and their lysis by cytotoxic T lymphocytes (CTL) and NK cells. Although the DNAM-1 ligand CD155 is ubiquitously expressed in various tissues, many human tumors significantly upregulate the expression of CD155; DNAM-1 on CTL and NK cells may be involved in tumor immunity. However, unlike those in mice, human tissues also express soluble isoforms of CD155 (sCD155) that lack the transmembrane region. Here, we show that sCD155 levels were significantly higher in the sera of 262 patients with lung, gastrointestinal, breast, and gynecologic cancers than in sera from healthy donors. In addition, the sCD155 levels were significantly higher in patients with early stage (stages 1 and 2) gastric cancer than in healthy donors, and were significantly higher in patients with advanced stage (stages 3 and 4) disease than in patients in those with early stage disease and healthy donors. Moreover, the sCD155 levels were significantly decreased after surgical resection of cancers. Thus, sCD155 level in serum may be potentially useful as a biomarker for cancer development and progression.